Pengaruh Kesadaran Merek, Asosiasi Merek, dan Loyalitas Merek terhadap Ekuitas Merek Lifebuoy - Dave Michael Chang Dave Michael Chang; Richard Andrew (Jurnal Riset Multidisiplin Edukasi, 2026)
This study aims to examine the influence of brand awareness, brand associations, and brand loyalty on the brand equity of Lifebuoy products. A descriptive quantitative approach with a cross-sectional design was applied in this research. The sample consisted of active Lifebuoy consumers who had used the product within the last six months. Data were collected through an online questionnaire, with 101 valid responses used for analysis. The data were processed using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) technique via SmartPLS 4. The findings reveal that the three independent variables, namely brand awareness, brand associations, and brand loyalty, positively influence Lifebuoy’s brand equity. These results indicate that the components of brand equity play a crucial role in strengthening the brand’s value and market position within the personal care industry. Thus, the study highlights the importance of marketing strategies that emphasize brand recognition, positive brand associations, and consumer loyalty to maintain competitive advantage.